Direct radiative impacts of desert dust on atmospheric water content. Issue 6 (3rd June 2018) - Spyrou, Christos
ABSTRACT: The direct and indirect radiative impact of naturally produced dust particles influences climate from regional to global scale, introducing one of the largest uncertainties in future climate projections. By absorbing and scattering solar radiation, aerosols reduce the amount of energy reaching the earth's surface, while at the same time they enhance the greenhouse effect by absorbing and emitting longwave radiation (direct dust effect). In this study an attempt is made to quantify the feedback of this energy redistribution in the atmospheric water content in the Arabian Peninsula (one of the main sources of atmospheric mineral dust globally). To this end the SKIRON/dust modeling system was used for 2 years (2014–2015) and two sets of simulations were performed: in the first one the dust particles exert no feedback on the radiative transfer due to dust particles (control run), while in the second set dust interacts with radiation (direct radiative effect). Both simulations have been evaluated in their ability to describe the impacts on surface humidity, with the simulations including the dust feedback showing improved results. These direct feedbacks lead to an increase in the mass of water in the atmospheric column that can reach a maximum daily average of 0.5 g per kg of dry air. Water vapor is the most important greenhouse gas and through this process dust enhances its own greenhouse effect, further increasing the surface temperature and humidity, making life difficult for people living in an already harsh desert climate. © 2018 American Association for Aerosol Research